Pengembangan Istrumen Asessmen Berbasis Literasi Numerasi Pada Materi Sudut Untuk Kelas IV SD - Nur Indah Utami; Nyiayu Fahriza Fuadiah; Nora Surmilasari (Katalis Pendidikan : Jurnal Ilmu Pendidikan dan Matematika, 2024)
The research carried out aims to produce a numeracy literacy-based assessment instrument in grade IV elementary school material that has been tested for validity and reliability, and has gone through systematic instrument analysis, namely by using a content validation test using the Lawse formula to calculate the Content Validity Ratio (CVR), empirical validity test using product moment correlation and reliability test using Cronbach's Alpha. This type of research is development research using the Plom model, the data collection method used is validation in the form of questionnaires and numeracy literacy tests. The research results obtained are: 1) the results of the validation of the questionnaire by CVR calculation experts stated that all the instruments created had a value of 1, which means they are valid; 2) the numeracy literacy-based assessment instrument developed is a reliable instrument with a reliability value of 0.5689 ≥ 0.413 (r_count ≥r_tabel); 3) from the student test results it was stated that 6 instruments were valid, namely instruments numbered 2, 3, 5, 6, 7 and 9. So the instrument developed produced an instrument that was suitable for use to measure student abilities.